Pengaruh Persepsi Layanan Informasi Terhadap Penyesuaian Diri Siswa Kelas VII SMP Kristen 1 Amanuban Timur: Indonesia - Rener Belly Maukari; Ferdinan L. Lopo; Juniati A. Maak; Yulinda Taebenu (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to determine the influence of students' perception of information services on the adjustment of seventh-grade students at SMP Kristen 1 Amanuban Timur. The research used a quantitative approach with a simple linear regression analysis method. The population consisted of all 95 seventh-grade students. The instrument used was a questionnaire that had been tested for validity and reliability. The results showed a significant influence of perception of information services on students' adjustment, with a contribution of 13.1%, while 86.9% was influenced by other factors beyond this study. The ANOVA test yielded an F-value of 13.987, which was greater than the F-table value of 3.943 (α = 0.05), indicating a positive and significant effect between the two variables. These findings suggest that a positive perception of information services can help improve students' ability to adapt to the school environment.